2011
DOI: 10.1080/00914037.2011.557811
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Study of Electrochemical Behavior of N-alkyl Substituted Polycarbazole Derivatives

Abstract: Poly(9-dodecylcarbazole) (PDDC) and poly[(9-dodecylcarbazole)-co-thiophene] (PDDCT) were synthesized via oxidative coupling method using FeCl 3 and the polymers exhibited good solubility in polar aprotic solvents. The synthesized polymers were characterized using UV-visible, FTIR, 1 H-NMR spectroscopic techniques. The polymers exhibited thermal stability up to 300 C. The absorption spectra showed the maximum absorption peak at 414 and 443 nm (k max ), respectively, for PDDC and PDDCT. The electrochemical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…RESULT AND DISCUSSIONS Synthesis, characterization, and study of thermal and electrochemical properties of PDDC and PDDCT are reported elsewhere [27]. The physical properties of the polymers are summarized in Table 1.…”
Section: Fabrication and Characterization Of Polymer Solar Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…RESULT AND DISCUSSIONS Synthesis, characterization, and study of thermal and electrochemical properties of PDDC and PDDCT are reported elsewhere [27]. The physical properties of the polymers are summarized in Table 1.…”
Section: Fabrication and Characterization Of Polymer Solar Cellmentioning
confidence: 99%
“…Poly(9-dodecylcarbazole) (PDDC) and poly[(9-dodecylcarbazole)-co-thiophene] (PDDCT) were synthesized by the process reported elsewhere [27]. These two polymers were used as donor material in fabricating polymeric solar cells and photovoltaic properties of the same were studied.…”
Section: Chemicals and Measurementsmentioning
confidence: 99%
“…While there are many studies reported on the electrodeposition of linear and dendrimeric forms of PVK, there appears to be a limited number of researches on hyperbranched PVK (Macit et al, 2005;Boudreault et al, 2010;Tria et al, 2010;Pokhrel et al,2011;. In this paper we report the synthesis of a new architecture of poly(Nvinylcarbazole) though reversible additionfragmentation chain transfer polymerization and the polymer's electrodeposition on a conducting substrate to form thin films.…”
Section: Introductionmentioning
confidence: 99%